Analisis Tingkat Pengetahuan Masyarakat Terhadap Penggunaan Antibiotik Di Apotek Berkah Muhammad Baranti Kabupaten Sidenreng Rappang - Arifuddin, Nur Ayu Safitri; Ramlan, Pratiwi; Febrianti, Devy (JUKEJ : Jurnal Kesehatan Jompa, 2025)
The increasing number of infection cases occurring today has led to a rise in antibiotic use among the public. Antibiotic use can be beneficial and effective when prescribed and consumed according to proper rules, dosage, and with wise judgment. However, antibiotic misuse among the public, such as non-compliance in taking antibiotics, is still common. Low levels of knowledge about medication can result in the failure to achieve therapeutic goals. Therefore, supervision and education from healthcare professionals regarding the function of antibiotics in treating infections are necessary. This study aims to analyze the public's level of knowledge regarding the use of antibiotics at Berkah Muhammad Pharmacy, Baranti, Sidenreng Rappang Regency. This research uses a quantitative method with a descriptive approach. The research subjects consisted of 110 respondents obtained using purposive sampling techniques. Data collection methods included observation, questionnaires, and documentation/literature study. Data analysis was performed using the Spearman rank test with the help of SPSS version 21. The results of the study showed that the levels of knowledge among respondents were as follows: good category – 8 respondents (7.27%), sufficient category – 26 respondents (23.64%), and poor category – 76 respondents (69.09%). The analysis of the relationship between the knowledge level variable and antibiotic use behavior showed a value of 0.363 with a p-value of 0.000 < 0.05, indicating a positive (+) correlation. This study shows that there is a significant relationship between knowledge and antibiotic use at Berkah Muhammad Pharmacy, Baranti, Sidenreng Rappang Regency.